Occurrence of Aceria tosichella in Brazil - Pereira, Paulo Roberto Valle da Silva (2010)
The objective of this work was to evaluate the occurrence of Aceria tosichella Keifer (Prostigmata: Eriophyidae), the wheat curl mite, in Rio Grande do Sul, Brazil. Samples to detect A. tosichella specimens were collected in wheat, corn, oat crops and potential host grasses in 46 localities, in October 2006, August and October 2007. Samples of wheat were also collected in experimental greenhouses at Embrapa Trigo, Passo Fundo, RS, Brazil. A. tosichella specimens were found in wheat samples from Passo Fundo, Palmeira das Missões, São Luís Gonzaga, and Santo Antônio das Missões, RS, Brazil. Symptoms due to A. tosichella infestations were observed only in greenhouse conditions. This is the first report of A. tosichella in Brazil and the second in South America.